2008
DOI: 10.1111/j.1600-051x.2008.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an injectable composite as a carrier for growth factor‐enhanced periodontal regeneration

Abstract: Characteristics of the PLGA composite makes it an attractive matrix to support native wound healing and rhGDF-5-enhanced periodontal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 74 publications
(71 reference statements)
2
31
0
3
Order By: Relevance
“…The rhGDF‐5/PLGA construct significantly increased bone and cementum formation in a dose‐dependent order in the absence of root resorption/ankylosis. To fully appreciate the effectiveness of rhGDF‐5 on periodontal wound healing/regeneration, biocompatible, biodegradable carriers, preferably synthetic should be used; carrier prerequisites including porosity for optimized cell ingrowth, space provision, and provision(s) for clot/wound stabilization have been emphasized (Polimeni et al 2006, Herberg et al 2008). Recent studies have shown that rhGDF‐5 soak loaded onto an absorbable collagen sponge carrier (rhGDF‐5/ACS) or adsorbed onto micro/macro‐porous β ‐TCP particles (rhGDF‐5/ β ‐TCP) significantly enhances periodontal wound healing/regeneration compared with sham‐surgery, carrier, and benchmark (rhPDGF/ β ‐TCP) controls (Kim et al 2009, Kwon et al 2010c, Lee et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rhGDF‐5/PLGA construct significantly increased bone and cementum formation in a dose‐dependent order in the absence of root resorption/ankylosis. To fully appreciate the effectiveness of rhGDF‐5 on periodontal wound healing/regeneration, biocompatible, biodegradable carriers, preferably synthetic should be used; carrier prerequisites including porosity for optimized cell ingrowth, space provision, and provision(s) for clot/wound stabilization have been emphasized (Polimeni et al 2006, Herberg et al 2008). Recent studies have shown that rhGDF‐5 soak loaded onto an absorbable collagen sponge carrier (rhGDF‐5/ACS) or adsorbed onto micro/macro‐porous β ‐TCP particles (rhGDF‐5/ β ‐TCP) significantly enhances periodontal wound healing/regeneration compared with sham‐surgery, carrier, and benchmark (rhPDGF/ β ‐TCP) controls (Kim et al 2009, Kwon et al 2010c, Lee et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…However, both the ACS and β ‐TCP carrier technologies are limited to inlay indications. The ease‐of‐use rhGDF‐5/PLGA composite construct herein is intended for inlay and onlay indications as well as minimally invasive procedures (Herberg et al 2008, Pompe 2008). A previous study, which focused on handling logistics, showed that the injectable rhGDF‐5/PLGA construct offered a simple predicable application to subgingival sites using a non‐critical‐size defect model (Kwon et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They should be injectable for ease-of-use implantable and minimally invasive approaches; they should be space-providing allowing structurally integrity/wound stability for a regenerate to form also in noncontained sites (onlay indications); they should be macroporous for rapid ingrowth of cells and vascular support from adjoining tissue resources; they should allow appropriate release/bioavailability of the biologic; and they should feature a biodegradation profile/rapid clearance allowing the regenerate uneventful maturation (Herberg et al 2008). …”
Section: Alternative Carrier Technologiesmentioning
confidence: 99%
“…92 Subsequently, this PLGA hydrogel was applied with recombinant human growth differentiation factor-5 (rhGDF-5) in periodontal defects in a dog model. 93 Periodontal pockets (3 · 6 mm, width · depth) are surgically created over the buccal roots of the second and fourth mandibular premolars in mongrel dogs.…”
Section: Stiff Biomaterialsmentioning
confidence: 99%